2017
DOI: 10.1016/j.ihj.2016.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Maternal hyperhomocysteinemia and congenital heart defects: A prospective case control study in Indian population

Abstract: Increased levels of maternal serum homocysteine are associated with increased risk of occurrence of congenital heart defects in their offsprings, suggesting that maternal hyperhomocysteinemia is an independent risk factor for congenital heart defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…Genetic and biochemical studies have shown that the preventive effect of folate is through lowering the level of hyperhomocysteinemia, which is a biomarker of oxidative stress and can induce the occurrence of CHD. 16,17 We found that the Hcy level was significantly elevated in the case group, indicating that oxidative stress may have increased in mothers of offspring with CHD.…”
Section: Discussionmentioning
confidence: 75%
“…Genetic and biochemical studies have shown that the preventive effect of folate is through lowering the level of hyperhomocysteinemia, which is a biomarker of oxidative stress and can induce the occurrence of CHD. 16,17 We found that the Hcy level was significantly elevated in the case group, indicating that oxidative stress may have increased in mothers of offspring with CHD.…”
Section: Discussionmentioning
confidence: 75%
“…Four case control studies (34)(35)(36)(37) reported associations between Neural tube defects and folate, vitamin B12 and homocysteine concentrations in the mother. Two studies reported other congenital anomalies (heart defects, orofacial cleft) (38,39) (Supplementary Table 3).…”
Section: Congenital Anomaliesmentioning
confidence: 99%
“…Maternal hyperhomocysteinemia was associated with increased risk for congenital heart defects (38). A study on risk factors for orofacial clefts (OFC) reported exclusive vegetarianism (proxy for low B12 status) to be a significant risk factor.…”
Section: Observational Studiesmentioning
confidence: 99%
“…И наконец, существует теория о влиянии негенетических факторов на развитие ассоциации ВПС и НБ, в частности, пренатальных стрессовых (метаболических) факторов, возможно, имеющих взаимосвязь с увеличением риска формирования ВПС и НБ, -гестационный сахарный диабет, гипергомоцистеинемия [24][25][26][27][28].…”
Section: рисунокunclassified